2019
DOI: 10.1021/acs.chemmater.9b01068
|View full text |Cite
|
Sign up to set email alerts
|

Rational Synthesis of Mixed-Metal Microporous Metal–Organic Frameworks with Controlled Composition Using Mechanochemistry

Abstract: Metal-Organic Frameworks Using Pre-Assembled Precursors. ChemRxiv. Preprint. Ball milling mechanochemistry enables enables targeted, rapid synthesis of mixed-metal metal-organic frameworks (MOFs) with controllable stoichiometric composition. Specifically, the use of ball milling enabled the use of pre-assembled coordination polymers of zinc, magnesium, nickel(II) and cobalt(II) as precursors in an innovative mechanochemical strategy for the deliberate assembly of mixed-metal MOF-74 materials comprised of pairs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 71 publications
0
83
0
1
Order By: Relevance
“…32 When the synthesis was performed in 1:1 nickel:ligand ratio and without heating, we were able to isolate [Ni(dhta)(H 2 O) 4 ]•2H 2 O coordination polymer (Ni-INT), which was recently detected and characterized as an intermediate for the mechanochemical preparation of mixed-metal MOF-74 materials. 39 Both products are highly crystalline, as could be seen in Electronic Supplementary Information (ESI) Fig. S1, and benchstable for months.…”
Section: Synthesis and Mechanical Processingmentioning
confidence: 86%
See 1 more Smart Citation
“…32 When the synthesis was performed in 1:1 nickel:ligand ratio and without heating, we were able to isolate [Ni(dhta)(H 2 O) 4 ]•2H 2 O coordination polymer (Ni-INT), which was recently detected and characterized as an intermediate for the mechanochemical preparation of mixed-metal MOF-74 materials. 39 Both products are highly crystalline, as could be seen in Electronic Supplementary Information (ESI) Fig. S1, and benchstable for months.…”
Section: Synthesis and Mechanical Processingmentioning
confidence: 86%
“…1d). 39 We were, however, more focused here on the response of Ni-MOF-74 to mechanical stress and the correlation between the electronic structure and magnetic properties of Ni-MOF-74 material depending on the level of internal crystal structure ordering. We found that evacuated Ni-MOF-74 collapses rapidly under mechanical stress imposed by ball-milling, producing stable mechanochemically-induced amorphous phase am-Ni-MOF-74.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible to use various types of metal sources, such as pure metals, metal oxides, metal hydroxides, metal carbonates, and even insoluble metals [114] . Furthermore, mechanochemical synthesis can be applied to a stoichiometric ratio of mixed distinct metal components to synthesize mixed-metal MOFs by milling [115] . However, if the byproducts also react under the employed conditions, a solvent may be necessary, as is the case for pore activation by solvent exchange.…”
Section: Mof Mass Production Processesmentioning
confidence: 99%
“…The pressure induced phase transitions and structural transformations may be advantageously used, for example, in high-pressure synthesis, mechanochemistry and nanotechnology. 35,[119][120][121][122][123][124][125][126][127][128][129][130][131][132][133] Mechanically responsible organic crystals showing macroscopic motion as a response to pressure or deformation are very interesting due to their potential applications in nanotechnology as organic actuators. 98,[130][131][132][133] The mechanical response of molecular crystals, polymers and organic materials related to living organism physiology is of direct and enormous interest for the human being.…”
Section: Introductionmentioning
confidence: 99%